Development of novel porous materials via polymer self-assembly and phase separation - Prochukhan, Nadezda (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2023)
Polymer self-assembly is an ever-growing field that is attracting interest from a diverse range of research topics, which include the production of functional devices and membranes for electronic, optical and energy applications, as well as more established areas such as filtration and separation. This interest stems from the environmentally friendly and low-cost nature of the `bottom-up? self-assembly process, when compared to more established top-down techniques. Nonetheless, there remain several challenges to implementing self-assembling systems into conventional manufacturing, especially in the case of novel membranes and nanostructures derived from biopolymers; these include gaps in research on controlling the self-assembly process, along with developing novel applications and devices using self-assembled materials. This thesis aims to address some of these limitations by closely examining the behavior and function of several self-assembling polymer systems. Chapter 1 details the background and rationale for this research. An overview of polymers, self-assembly, membranes, polymer brushes and block-copolymers (BCPs) which are used in the work are provided. The subsequent chapters look at experimental approaches aimed at tackling some of the challenges associated with membrane and porous film production technologies in an eco-friendly manner. Chapter 2 examines the problem of large-scale membrane production in a financially and an environmentally viable manner. A widely recycled polymer poly(methyl methacrylate) (PMMA) and a biopolymer chitosan are employed for membrane fabrication. A custom-built apparatus is used to promote membrane formation by thermally induced phase separation (TIPS) and water vapour induced phase separation (VIPS). These methods are designed to limit solvent and material waste and reduce energy costs by using low electricity and temperatures. Furthermore, a strategy to produce thoroughly functionalized PMMA is provided via silanization with (3-aminopropyl)triethoxysilane (APTS). Another challenge is to characterize 3D materials; thus, a Focused Ion Beam (FIB-SEM) tomography is detailed as a method to analyze these morphologically complex systems. These membranes were also tested for their tensile properties and filtration capability using Evans Blue dye in order to demonstrate their functional capacity. Chapter 3 focuses primarily on the reproducibility of pore sizes and asymmetry with the aim to fabricate novel porous systems with the least waste possible. A block copolymer polystyrene-b-poly(ethylene oxide) (PS-b-PEO) self-assembly is investigated using water vapour annealing (WVA) at room conditions as a sustainable processing methodology. The resultant toroidal micelles display pore sizes of ~ 400 ? 600 nm with uniform shape-characteristics. To demonstrate a practical application, the micellar morphology is used for pattern transfer to produce silicon nanotube arrays. Despite the low amounts of polymer and solvents being employed, it is crucial to utilize the most ecologically competitive methods and materials. Chapter 4 takes a similar approach to Chapter 3, but uses lignin, a highly abundant biopolymer, to produce membranes with high fidelity. Chapter 3 details the self-assembly of four different lignin materials into membranes facilitated by the WVA. The membrane systems are optimized for production of black silicon (BSi) which exhibits low reflectivity in the visible region. This approach opens up avenues for large-scale biopolymer membrane fabrication using cheap and abundant chemicals (lignin and water) for solar cell technology and potentially other applications. Chapter 5 outlines the main findings in this work in context of the goals and achievements in this thesis. A future perspective and direction for research is provided with the aim of focusing on environmentally sustainable methods from the onset of material design.
APPROVED
Keywords: polymer; biopolymer; self-assembly; phase separation; phase inversion